Gazing at Eurydice: Authorship and Otherness in Bracha L. Ettinger - Kisiel, Anna (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2020)
A historical photograph of women and children from the Mizocz ghetto taken in 1942 just before their execution constitutes one of the most recurring motifs in Bracha L. Ettinger’s visual art. By means of her artworks, Ettinger endeavours to retrieve these women’s dignity and work through their traumas at a point when they are unable to do it themselves. Yet, one cannot ignore a number of questions that arise in the context of this kind of aesthetic practice; after all, Ettinger uses an archival photograph, taken by an anonymous photographer, and her acts of altering and decontextualising this “ready-made” material are aimed at producing a certain artistic effect. The objective of this article is to reflect on the issue of authorship in Bracha L. Ettinger’s theory and art. Having introduced two Eurydicial artworks, I proceed to unravel the status of a matrixial artist-author. In order to do so, I analyse such notions as ready-made art, matrixial Otherness, trauma of the World, gaze, and appropriation.